Основні підсумки розкопок у маловивчених частинах Ольвійського городища - Крижицький, С.Д. (Археологія, 2015)
Статтю присвячено публікації головних результатів пошукових розкопок, що провадилися у другій половині минулого століття Ольвійською експедицією Інституту археології АН УРСР. The expedition of the Institute of Archaeology of the Academy of Sciences, USSR, conducted a cycle of archaeological prospecting excavations at Olbian hill-fort from the 1950s to the 1980s. Part of them were continued later and allowed obtaining the grand-scale comprehensive results which were relatively full presented in print. The other part of these excavations due to various reasons was not developed and the works at those areas were seized. Closed were the excavation areas at the north-western sector of the hill-fort («С-З») and at the extension of the Main longitudinal street to the north from «АГД» area («В-V»), at the central eminence f the Upper City («Р-19»); excavation areas in the centre («НГЦ») and to the north from the centre («НГС-ю») in the Lower City, and excavation areas in the terraced area of Olbia («Т-1», «Т-2»). Nevertheless, during the work at these areas, were made the observations worth attention which altogether allowed specifying a series of moments in historic topography of the hill-fort and obtaining the idea on the stratigraphy and building remains at the hill-fort areas not studied before. The aim of this paper is to describe briefly the obtained results of these works and to determine the possible most perspective directions of the excavations which can be continued at these areas in future. В пятидесятые—восьмидесятые годы прошлого века экспедицией ИА АН УССР на Ольвийском городище был проведен цикл разведочных раскопок. Часть из них были продолжены в дальнейшем и позволили получить масштабные комплексные результаты, нашедшие относительно полное отражение в печати. Другая часть по разным причинам дальнейшего развития не получила, и работы на этих участках были прекращены. Были закрыты раскопы в северо-западном секторе городища («С-З») и на продолжении Главной продольной улицы к северу от участка «АГД» («В-V»); на центральной возвышенности Верхнего города («Р-19»); раскопы в центре («НГЦ») и к северу от центра («НГС-ю») в Нижнем городе; раскопы в террасной части Ольвии («Т-1», «Т-2»). Тем не менее, в ходе работ на этих участках были сделаны заслуживающие внимания наблюдения, которые в комплексе позволили уточнить ряд моментов исторической топографии городища и получить представление о стратиграфии и строительных остатках на участках городища, ранее не исследовавшихся. В задачу настоящей публикации входит краткая характеристика полученных результатов работ и определение возможных наиболее перспективных направлений продолжения раскопок этих участков в будущем.